The use of natural rubber latex as a renewable and sustainable modifier of asphalt binder - Wen, Yong; Wang, Yuhong; Zhao, Kecheng; Sumalee, Agachai (My University, 2017)
Natural rubber (NR) powder as a bio-modifier of asphalt binder has been shown to have some beneficial effects. However, there is limited research into the use of the liquid form of NR, i.e. concentrated NR latex, as an asphalt binder modifier. Compared to NR powder, NR latex is cheaper and more accessible in some countries, and potentially creates viscosity-reducing foams in the modified binder during mixture production. In this research, asphalt binders modified with different amount of NR latex were systematically studied, including the rotational viscosities, rutting resistance, fatigue resistance, low-temperature behaviour and temperature sensitivity. The dispersion of the NR latex in the modified binders was examined using fluorescence microscope and atomic force microscope. Test results indicate that the addition of NR latex increases the viscosity and elastic recovery of the modified binders and potentially enhances asphalt pavements’ resistance to rutting, thermal cracking and fatigue damage. The NR latex also reduces the temperature sensitivity of the modified binders. The optimum NR latex content was found to be 7% of the total mass of the modified binder. A network of extensive microstructures mixed with bubbles was identified in the modified binders under heat. As a renewable and sustainable material, NR latex has the potential to be used as an effective asphalt modifier.
Keywords: atomic force microscope (AFM); fluorescence microscope; multiple stress creep recover (MSCR); Natural rubber latex; rheological properties; rubber-modified asphalt